Relationship of Calorie Breakfast with the School Age Child Concentration Ability in Elementary School 3 Canggu 2012 - Sri Ayu Ari Susanthi (Coping: Community of Publishing in Nursing, 2013)
Concentration is paramount in every individual, especially the students. Concentration is influenced by several factors one of which is calorie breakfast in the morning. A good breakfast calories can meet the needs of the body so the body can continue to optimal metabolism. This study aims to assess the relationship between calorie breakfast with students' ability to concentrate. This study used a descriptive correlational research design with a cross sectional approach. Sample consisted of 51 people selected by purposive sampling of students who aged 10-12 years. Data collection using a live interview during the 4 days of calorie breakfast and measurement of concentration by the Bourdon Wiersma test, then analyzed with a bivariate correlation test Product Moment and Spearman Rank (p <0.05). The results of this study show that the average calorie breakfast are 306,17 kcal, whereas the average concentration ability (speed) is 10,7174, the average concentration ability (constancy) was 4,2549, and the average concentration ability (accuracy ) is 5,51. The results of bivariate analysis obtained p-value = 0.000 with a coefficient correlation is -0,541, that means there is a intermediate relationship between calorie breakfast with the ability to concentrate (speed), p value = 0,000 with a coefficient correlation is -0,608, that means there is a strong link between calorie breakfast with ability to concentrate (constancy), and p value = 0,033 with a coefficient correlation is -0,299, that means there is a low relationship between calorie breakfast with the ability of concentration (accuracy). On this research can be concluded that there was a significant negative correlation between calorie breakfast with the ability to concentrate, that means the better calorie breakfast the score the lower the calorie breakfast concentration ability, which means the better the child's ability to concentrate.